Red nitride fluorescent powder as well as preparation method and application thereof

By adding Li and Si to Sr2[MgAl5N7]:Eu2+, the lattice rigidity was enhanced, and the Sr2[Mg1-xLixAl5-xSixN7]:yEu2+ type red nitride phosphor was developed, which solved the narrow peak red phosphor in high-power density light source. The brightness saturation and thermal saturation problems under the radiance saturation achieve high color gamut display and high efficiency fluorescence performance.

CN119391407AActive Publication Date: 2025-02-07LANZHOU UNIV

Patent Information

Application Number
CN202411469067.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-07
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The existing narrow peak red phosphors exhibit brightness saturation and thermal saturation problems under high power density light sources, and their preparation is unfriendly to the environment, low quantum efficiency outside the luminescent, poor moisture resistance, and difficult to meet the needs of laser display applications.

Method used

The chemical composition of Sr2[Mg1-xLixAl5-xSixN7]:yEu2+ is adopted to enhance the lattice rigidity by adding Li and Si equilibrium charges, thereby improving the quantum efficiency and luminescence thermal stability of the phosphor. This phosphor shows excellent red light emission under blue light excitation and is suitable for high-color gamut laser display devices.

Benefits of technology

The red light emission with high color gamut display is achieved, the external quantum efficiency is improved to 42.0%, the thermal stability is increased to 67.0% at 150°C, and the preparation method is simple and easy to industrially produce.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391407A_ABST
    Figure CN119391407A_ABST
Patent Text Reader

Abstract

The invention provides red nitride fluorescent powder as well as a preparation method and application thereof, and belongs to the technical field of rare earth luminescent materials. The chemical composition of the red nitride fluorescent powder is Sr2 [Mg < 1-x > Li < x > Al < 5-x > Si < x > N < 7 >]: yEu < 2 + >, x is greater than or equal to 0.001 and less than or equal to 0.50, and y is greater than or equal to 0.0005 and less than or equal to 0.20. The fluorescent powder is a nitride system, has strong light absorption when blue light is 400-500nm, has an excitation peak value of about 460nm, can be effectively excited by blue laser, can emit red fluorescence when being excited by blue light, has an emission peak value adjustable in a range of 635-685nm and a half-peak width adjustable in a range of 75-90nm, and has a good contribution to a high color gamut in a display device. When the fluorescent powder is used in various laser display devices taking blue light high-power laser as an excitation source, the fluorescent powder has the advantages of high luminance, high luminous efficiency and stable physical and chemical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rare earth luminescent materials, and in particular to a red nitride phosphor and a preparation method and application thereof. Background Art

[0002] The development and progress of display technology has changed people's lives, and the medium of long-distance communication has evolved from pure text and sound to vivid images. For display devices, efficient light sources have been increasingly used in displays. Display devices require efficient narrow-peak emission phosphors, that is, the required phosphors are required to have a narrow emission band with a full width that is half maximum (FWHM), a specific peak position, high quantum efficiency and good thermal stability. The current commercial liquid crystal display (LCD) backlight source uses "blue light InGaN chip + β-SiAlON:Eu 2+ (λ em =540nm; FWHM = 55nm) green phosphor + K2SiF6:Mn 4+ (λ em=630nm, peak) red phosphor" packaging solution is the current commercial solution with the largest color gamut area based on phosphor technology. The color gamut is mainly determined by the color coordinates of red, green and blue (RGB) light emitted by the light emitting diode (LED) light source. The traditional display technology uses LCD, and its core technology is the use of LED as the backlight. However, there are some problems with LED as a backlight, such as large optical extension, low brightness, insufficient color purity, etc., which greatly limit the use of display devices in high-brightness and wide-color gamut display fields, such as theaters, projection equipment, etc. The laser light source technology that has emerged in recent years belongs to the same solid-state light source technology as the LED light source technology. Due to its advantages such as long life, low energy consumption and environmental friendliness, it is also considered by academia and industry to be the most promising green light source in the 21st century. Because the emission bandwidth of the laser is short, it means high efficiency, small size and low power consumption per unit laser diode (laser The red, green and blue lasers can achieve high-purity laser display, but the current green laser equipment is not only expensive but also has a problem called "green defect", and the design of the multi-emission system naturally increases the cost. Therefore, the solution of using blue laser and multi-color phosphor materials to achieve display is more efficient and more valuable for research. For devices using phosphors, the quality of the phosphors is the key to determining the performance of the device. Laser display technology still mainly uses the phosphors of traditional LED technology, but considering the brightness saturation phenomenon of phosphors under high power density light sources, there are differences in the requirements for phosphors for lasers and phosphors for LEDs.

[0003] For narrow peak red phosphors, the narrowest Eu 2+ Activated Sr[LiAl3N4]:Eu 2+ The emission of phosphor is at 650nm and the FWHM is 50nm, but its water stability is very poor, which seriously reduces the performance of the device packaged with it. 4+ Activated luminescent materials (spike emission) have become the first choice for wide color gamut display phosphors. Among them, commercial wide color gamut red powder is based on K2SiF6:Mn 4+ Fluoride systems are representative, with narrow peak luminescence, but there are problems such as environmental unfriendly preparation, low external quantum efficiency (<55%), and poor moisture resistance, which need to be solved urgently. More importantly, for laser light source technology, Mn 2+ and Mn 4+Activated narrow-peak red phosphors have serious problems of light-induced saturation and thermal saturation, and the light saturation threshold and light efficiency are too low to meet the requirements of laser display applications. In general, the narrow-peak red luminescent materials currently developed at home and abroad generally have problems such as low light efficiency and poor reliability. Therefore, high-efficiency phosphors with high-efficiency narrow-peak emission have become the key to technical research and a hot spot in the display market. It is urgent to develop an effective construction method for high-efficiency narrow-peak phosphors for display to break through the bottleneck of lack of key materials. Summary of the invention

[0004] The object of the present invention is to provide a red nitride phosphor and a preparation method and application thereof. The red nitride phosphor has excellent red light emission, its emission can achieve a high color gamut, and is easy to synthesize.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a red nitride phosphor, the chemical composition of which is Sr2[Mg 1-x Li x Al 5-x Si x N7]:yEu 2+ , where 0.001≤x≤0.50, 0.0005≤y≤0.20.

[0007] Preferably, x=0.02-0.4, y=0.01-0.06.

[0008] The present invention provides a method for preparing the red nitride phosphor described in the above technical solution, comprising the following steps:

[0009] According to the required stoichiometric ratio, a nitrogen-containing Sr source, a nitrogen-containing Mg source, a nitrogen-containing Al source, a nitrogen-containing Si source, a Li source and a Eu source are mixed and ground to obtain a mixed material;

[0010] After sintering, the mixed material is ground and sieved in sequence to obtain red nitride phosphor.

[0011] Preferably, the Li source is lithium nitride or lithium aluminum hydride; the Eu source is europium fluoride or europium nitride or europium oxide.

[0012] Preferably, the sintering pressure is 0-1.0 MPa, and the sintering atmosphere is nitrogen or a nitrogen-hydrogen mixed gas.

[0013] Preferably, the nitrogen-hydrogen mixed gas is a mixture of 90% nitrogen and 10% hydrogen by volume percentage.

[0014] Preferably, the sintering temperature is 1100-1600° C., and the holding time is 2-20 hours.

[0015] The present invention provides the use of the red nitride phosphor described in the above technical solution or the red nitride phosphor prepared by the preparation method described in the above technical solution in a laser display device of a blue laser.

[0016] The present invention provides the use of the red nitride phosphor described in the above technical solution or the red nitride phosphor prepared by the preparation method described in the above technical solution in a blue light excited liquid crystal display.

[0017] The present invention provides a red nitride phosphor, the chemical composition of which is Sr2[Mg 1-x Li x Al 5-x Si x N7]:yEu 2+ , wherein 0.001≤x≤0.50, 0.0005≤y≤0.20. 2+ Li and Si are added simultaneously to balance the charge, and the lattice is contracted to enhance the lattice rigidity. The enhanced lattice rigidity can improve the quantum efficiency and thermal stability of luminescence. The phosphor is a nitride system, which has strong light absorption in the blue light of 400-500nm, and the excitation peak is around 460nm. It can be effectively excited by a blue laser and can emit red fluorescence under blue light excitation. The emission peak is adjustable at 635-685nm, and the half-peak width is adjustable at 75-90nm, which makes a good contribution to the high color gamut in the display device. The phosphor is used in various laser display devices with a blue high-power laser as the excitation source. It has the advantages of strong luminous brightness, high luminous efficiency, and stable physical and chemical properties, meeting the performance requirements of high-performance devices. The results of the embodiment show that compared with the sample SMAN:0.01Eu without adding Li and Si 2+ , the sample with Li and Si added at the same time SMAN-0.1LS:0.01Eu 2+ The external quantum efficiency increased from 28.1% to 42.0%, and the thermal stability at 150°C increased from 58.9% to 67.0%.

[0018] The red nitride phosphor of the present invention is prepared by a high-temperature solid-phase method, and the preparation method is simple, easy to operate, highly controllable, stable in performance, and easy to industrialize and produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 XRD spectra of the phosphors prepared in Examples 1 to 4 (a to d correspond to Examples 1 to 4, respectively) and standard spectra (s);

[0020] Figure 2 The excitation spectra and emission spectra of the phosphors prepared in Examples 1 to 4 (a to d correspond to Examples 1 to 4, respectively);

[0021] Figure 3 The graph of the emission spectrum of the phosphor prepared in Example 1 as a function of temperature;

[0022] Figure 4 The performance of the phosphor prepared in Example 1 under high-power blue laser excitation, wherein (a) is a curve diagram showing the luminous flux of the rotating phosphor wheel encapsulated with the phosphor prepared in Example 1 as the incident laser power density increases; (b) is the emission spectrum of the phosphor sample prepared in Example 1 under different laser power excitations;

[0023] Figure 5 XRD spectra of the phosphors prepared in Examples 5 to 6 (a to b correspond to Examples 5 to 6, respectively) and standard spectra (s);

[0024] Figure 6 The excitation spectrum and emission spectrum of the phosphors prepared in Examples 5 and 6 (a to b correspond to Examples 5 and 6 respectively);

[0025] Figure 7 The XRD spectrum and standard spectrum of the phosphor prepared in Comparative Example 1;

[0026] Figure 8 The excitation spectrum and emission spectrum of the phosphor prepared in Comparative Example 1;

[0027] Fig. 9 The figure is a comparison chart of the luminescence thermal stability of the phosphors prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0028] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0029] The present invention provides a red nitride phosphor, the chemical composition of which is Sr2[Mg 1-x Li x Al 5-x Si x N7]:yEu 2+ ((Recorded as SMAN-xLS:yEu 2+ )), where 0.001≤x≤0.50, 0.0005≤y≤0.20.

[0030] In the present invention, x is preferably 0.02 to 0.4, more preferably 0.1 to 0.3, and still more preferably 0.1, and y is 0.01 to 0.06, and more preferably 0.03 to 0.05.

[0031] The present invention provides a method for preparing the red nitride phosphor described in the above technical solution, comprising the following steps:

[0032] According to the required stoichiometric ratio, a nitrogen-containing Sr source, a nitrogen-containing Mg source, a nitrogen-containing Al source, a nitrogen-containing Si source, a Li source and a Eu source are mixed and ground to obtain a mixed material;

[0033] After sintering, the mixed material is ground and sieved in sequence to obtain red nitride phosphor.

[0034] In the present invention, the nitrogen-containing Sr source is preferably strontium nitride; the nitrogen-containing Mg source is preferably magnesium nitride; the nitrogen-containing Al source is preferably aluminum nitride; and the nitrogen-containing Si source is preferably silicon nitride.

[0035] In the present invention, the Li source is preferably lithium nitride or lithium aluminum hydride; the Eu source is preferably europium fluoride or europium nitride or europium oxide.

[0036] The present invention preferably mixes all materials in an air-tight glove box to form a mixture, and grinds to obtain a mixed material; the present invention has no particular limitation on the grinding, and the grinding can be carried out according to a process well known in the art.

[0037] In the present invention, the mixed material is preferably placed in a tungsten crucible, a molybdenum crucible or a boron nitride crucible for sintering.

[0038] In the present invention, the sintering pressure is preferably 0-1.0 MPa, more preferably 0.5 MPa, and the sintering atmosphere is preferably nitrogen or a nitrogen-hydrogen mixed gas.

[0039] In the present invention, the nitrogen-hydrogen mixed gas is preferably a mixture of 90% nitrogen and 10% hydrogen by volume percentage.

[0040] In the present invention, the sintering temperature is preferably 1100-1600° C., more preferably 1200-1500° C., more preferably 1300° C., and the holding time is preferably 2-20 h, more preferably 5-15 h, further preferably 6-10 h.

[0041] After the sintering, the present invention preferably cools to room temperature, grinds the obtained sintered product, and sieves it to obtain a red nitride phosphor. The present invention has no special limitation on the grinding and sieving, and can be carried out according to the process well known in the art.

[0042] The present invention provides the use of the red nitride phosphor described in the above technical solution or the red nitride phosphor prepared by the preparation method described in the above technical solution in a laser display device of a blue laser.

[0043] The present invention provides the use of the red nitride phosphor described in the above technical solution or the red nitride phosphor prepared by the preparation method described in the above technical solution in a blue light excited liquid crystal display.

[0044] The present invention has no particular limitation on the application method, and the application can be carried out according to methods well known in the art.

[0045] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0046] Example 1

[0047] According to the chemical formula SMAN-0.1LS:0.01Eu 2+ The stoichiometric ratio of each raw material is as follows: Sr3N2, Mg3N2, Li3N, Si3N4, AlN and EuF3 (the purity of all raw materials is above 99.5%) are weighed respectively, the raw materials are mixed to form a mixture, and after being ground and mixed evenly, they are placed in a tungsten crucible, and placed in a high-temperature and high-pressure furnace under a nitrogen atmosphere, the sintering pressure is 0.5MPa, and it is fired at 1300℃ for 6h, and then cooled to room temperature, ground, and sieved to obtain a red nitride phosphor SMAN-0.1LS:0.01Eu 2+ (i.e. Sr2[Mg 1-x Li x Al 5-x Si x N7]:yEu 2+ , x=0.1, y=0.01).

[0048] Figure 1 (a, s) are the XRD patterns of the phosphor prepared in Example 1 and the calculated standard patterns. Figure 1 It can be seen that the XRD spectrum of the phosphor prepared in Example 1 is compared with the standard spectrum of the standard SMAN. It can be seen that due to the lattice contraction, most of the diffraction peaks are shifted to large angles, and no impurity peaks appear, indicating that the substitution ions successfully enter the lattice, that is, the phosphor synthesized in Example 1 is single-phase and high in purity.

[0049] Figure 2 (a) is the excitation spectrum and emission spectrum of the phosphor prepared in Example 1, Figure 2 The inset is a local magnified view of the emission spectrum. Figure 2 The monitoring wavelength of the excitation spectrum in (a) is 654 nm. It can be seen that the phosphor prepared in Example 1 can be excited by wavelengths in the range of 250-380 nm and 400-500 nm. The excitation spectrum is a wide spectrum covering the ultraviolet and blue light regions. The excitation peak is located near 460 nm, and the spectrum peak is high, indicating that the phosphor prepared in Example 1 can be effectively excited by blue light. Figure 2 In the emission spectrum of (a), the excitation wavelength is 460nm and the emission peak is Eu 2+The emission peak is located near 654nm and the FWHM is 79nm. The external quantum efficiency of the phosphor sample prepared in Example 1 is 42.0%. The above shows that the phosphor prepared in Example 1 is suitable for making red phosphor for high color gamut laser display.

[0050] Figure 3 The graph of the emission spectrum of the phosphor prepared in Example 1 as a function of temperature shows that the luminous intensity of the phosphor gradually decreases as the temperature increases, and the intensity at 100°C can be maintained at 78.7% of the intensity at room temperature (the operating temperature of the phosphor wheel device encapsulated with the phosphor sample is 50-100°C).

[0051] Figure 4 The performance of the phosphor prepared in Example 1 under high-power blue laser excitation, wherein (a) is a curve of the luminous flux of the rotating phosphor wheel encapsulated with the phosphor prepared in Example 1 as the incident laser power density increases. Figure 4 As shown in (a), as the laser power increases, the device has luminescence saturation. This is partly because the thermal quenching of heat cannot be completely eliminated, and more importantly, it is due to laser excitation quenching. Although luminescence saturation cannot be avoided, the luminescence saturation threshold of the phosphor sample prepared in Example 1 is very high, reaching 52.22W / mm 2 , which is better than the saturation threshold of all existing red phosphors, as shown in Table 1. Figure 4 (b) shows the emission spectra of the phosphor sample prepared in Example 1 under different laser powers. As the laser power increases, the emission intensity of the phosphor sample prepared in Example 1 increases before reaching the saturation threshold, and decreases after exceeding the saturation threshold.

[0052] Table 1 Comparison of the laser excitation performance of the phosphor prepared in Example 1 with that of the existing phosphors

[0053]

[0054] [1]J.Zhou,Y.Wang,Y.Chen,Y.Zhou,B. L. Zhou, J. Yan, J. Shi, R.-S. Liu, M. Wu, Angewandte Chemie International Edition 2021, 60, 3940-3945.

[0055] [2]HLSi Sc,J.Wang,Chinese Journal of Luminescence 2021,42,1549-1558.

[0056] [3]Y.Zhou,H.Ming,Y.Zhao,Y.Wang,E.Song,Z.Xia,Q.Zhang,Chinese Journalof Luminescence 2021,42,1559-1568.

[0057] [4]Y.Zhou,C.Yu,E.Song,Y.Wang,H.Ming,Z.Xia,Q.Zhang,Advanced OpticalMaterials 2020,8,2000976.

[0058] [5]S.B.Kwon,B.Y.Kim,S.H.Choi,J.H.Yoo,W.H.Kim,J.P.Kim,H.J.Jeong,D.J.Park,B.K.Kang,D.H.Yoon,Y.H.Song,Current Applied Physics 2020,20,1281-1287.

[0059] [6]Y.Zhang,Z.Zhang,X.Liu,G.Shao,L.Shen,J.Liu,W.Xiang,X.Liang,Chemical Engineering Journal 2020,401,125983.

[0060] [7]S.Li,D.Tang,Z.Tian,X.Liu,T.Takeda,N.Hirosaki,F.Xu,Z.Huang,R.-J.Xie,Journal of Materials Chemistry C 2017,5,1042-1051.

[0061] [8]X.Peng,S.Li,Z.Liu,B.Zhang,Y.Peng,D.Yu,R.Tian,X.Yao,Z.Huang,X.Liu,R.-J.Xie,Journal of the European Ceramic Society 2021,41,5650-5657.

[0062] [9]T.Hu,L.Ning,Y.Gao,J.Qiao,E.Song,Z.Chen,Y.Zhou,J.Wang,M.S.Molokeev,X.Ke,Z.Xia,Q.Zhang,Light:Science&Applications 2021,10,56.

[0063] Example 2

[0064] According to the chemical formula SMAN-0.2LS:0.01Eu 2+ The stoichiometric ratio of each raw material is as follows: Sr3N2, Mg3N2, Li3N, Si3N4, AlN and EuF3 (the purity of all raw materials is above 99.5%) are weighed respectively, the raw materials are mixed to form a mixture, and after being ground and mixed evenly, they are placed in a tungsten crucible, and placed in a high-temperature and high-pressure furnace under a nitrogen atmosphere, the sintering pressure is 0.5MPa, and it is fired at 1300℃ for 6h, then cooled to room temperature, ground, and sieved to obtain a red nitride phosphor SMAN-0.2LS:0.01Eu 2+ (i.e. Sr2[Mg 1- x Li x Al 5-x Si x N7]:yEu 2+ , x=0.2, y=0.01).

[0065] Figure 1 (b, s) are the XRD patterns of the phosphor prepared in Example 2 and the calculated standard patterns. Figure 1 It can be seen that the XRD spectrum of the phosphor prepared in Example 2 is compared with the standard spectrum of the standard SMAN. It can be seen that due to the lattice contraction, most of the diffraction peaks are shifted to large angles, and no impurity peaks appear, indicating that the substitution ions successfully enter the lattice, that is, the phosphor synthesized in Example 2 is single-phase and high in purity.

[0066] Figure 2 (b) is the excitation spectrum and emission spectrum of the phosphor prepared in Example 2. Figure 2 The monitoring wavelength of the excitation spectrum in (b) is 651 nm. It can be seen that the phosphor prepared in Example 2 can be excited by wavelengths in the range of 250-380 nm and 400-500 nm. The excitation spectrum is a wide spectrum covering the ultraviolet and blue light regions. The excitation peak is located near 460 nm, and the spectrum peak is high, indicating that the phosphor prepared in Example 2 can be effectively excited by blue light. Figure 2 In the emission spectrum of (b), the excitation wavelength is 460nm and the emission peak is Eu 2+ The emission peak is located near 651nm and the FWHM is 79nm, which indicates that the phosphor prepared in Example 2 is suitable for making red phosphor for high color gamut laser display.

[0067] Example 3

[0068] According to the chemical formula SMAN-0.3LS:0.01Eu 2+The stoichiometric ratio of each raw material is as follows: Sr3N2, Mg3N2, Li3N, Si3N4, AlN and EuF3 (the purity of all raw materials is above 99.5%) are weighed respectively, the raw materials are mixed to form a mixture, and after being ground and mixed evenly, they are placed in a tungsten crucible, and placed in a high-temperature and high-pressure furnace under a nitrogen atmosphere, the sintering pressure is 0.5MPa, and it is fired at 1300℃ for 6h, and then cooled to room temperature, ground, and sieved to obtain a red nitride phosphor SMAN-0.3LS:0.01Eu 2+ (i.e. Sr2[Mg 1- x Li x Al 5-x Si x N7]:yEu 2+ , x=0.3, y=0.01).

[0069] Figure 1 (c, s) are the XRD patterns of the phosphor prepared in Example 3 and the calculated standard patterns. Figure 1 It can be seen that the XRD spectrum of the phosphor prepared in Example 3 is compared with the standard spectrum of the standard SMAN. It can be seen that due to the lattice contraction, most of the diffraction peaks are shifted to large angles, and no impurity peaks appear, indicating that the substituted ions successfully enter the lattice, that is, the phosphor synthesized in Example 3 is single-phase and high in purity.

[0070] Figure 2 (c) is the excitation spectrum and emission spectrum of the phosphor prepared in Example 3. Figure 2 The monitoring wavelength of the excitation spectrum in (c) is 649 nm. It can be seen that the phosphor prepared in Example 3 can be excited by wavelengths in the range of 250-380 nm and 400-500 nm. The excitation spectrum is a wide spectrum covering the ultraviolet and blue light regions. The excitation peak is located near 460 nm, and the spectrum peak is high, indicating that the phosphor prepared in Example 3 can be effectively excited by blue light. Figure 2 In the emission spectrum of (c), the excitation wavelength is 460nm and the emission peak is Eu 2+ The emission peak is located near 649nm and the FWHM is 79nm, which indicates that the phosphor prepared in Example 3 is suitable for making red phosphor for high color gamut laser display.

[0071] Example 4

[0072] According to the chemical formula SMAN-0.4LS:0.01Eu 2+The stoichiometric ratio of each raw material is as follows: Sr3N2, Mg3N2, Li3N, Si3N4, AlN and EuF3 (the purity of all raw materials is above 99.5%) are weighed respectively, the raw materials are mixed to form a mixture, and after being ground and mixed evenly, they are placed in a tungsten crucible, and placed in a high-temperature and high-pressure furnace under a nitrogen atmosphere, the sintering pressure is 0.5MPa, and it is fired at 1300℃ for 6h, and then cooled to room temperature, ground, and sieved to obtain a red nitride phosphor SMAN-0.4LS:0.01Eu 2+ (i.e. Sr2[Mg 1- x Li x Al 5-x Si x N7]:yEu 2+ , x=0.4, y=0.01).

[0073] Figure 1 (d, s) are the XRD patterns of the phosphor prepared in Example 4 and the calculated standard patterns. Figure 1 It can be seen that the XRD spectrum of the phosphor prepared in Example 4 is compared with the standard spectrum of the standard SMAN. It can be seen that due to the lattice contraction, most of the diffraction peaks are shifted to large angles, and no impurity peaks appear, indicating that the substituted ions successfully enter the lattice, that is, the phosphor synthesized in Example 4 is single-phase and high in purity.

[0074] Figure 2 (d) is the excitation spectrum and emission spectrum of the phosphor prepared in Example 4. Figure 2 The monitoring wavelength of the excitation spectrum in (d) is 647 nm. It can be seen that the phosphor prepared in Example 4 can be excited by wavelengths in the range of 250-380 nm and 400-500 nm. The excitation spectrum is a wide spectrum covering the ultraviolet and blue light regions. The excitation peak is located near 460 nm, and the spectrum peak is high, indicating that the phosphor prepared in Example 4 can be effectively excited by blue light. Figure 2 In the emission spectrum of (d), the excitation wavelength is 460nm and the emission peak is Eu 2+ The emission peak is located near 647nm and the FWHM is 78nm, which indicates that the phosphor prepared in Example 4 is suitable for making red phosphor for high color gamut laser display.

[0075] Example 5

[0076] According to the chemical formula SMAN-0.02LS:0.05Eu 2+The stoichiometric ratio of each raw material is as follows: Sr3N2, Mg3N2, Li3N, Si3N4, AlN and EuF3 (the purity of all raw materials is more than 99.5%) are weighed respectively, the raw materials are mixed to form a mixture, and after grinding and mixing evenly, the mixture is placed in a tungsten crucible, and then placed in a high-temperature and high-pressure furnace under a nitrogen atmosphere, the sintering pressure is 0.5MPa, and it is fired at 1300℃ for 6h, then cooled to room temperature, ground, and sieved to obtain a red nitride phosphor SMAN-0.02LS:0.05Eu 2+ (i.e. Sr2[Mg 1-x Li x Al 5-x Si x N7]:yEu 2+ , x=0.02, y=0.05).

[0077] Figure 5 (a, s) are the XRD patterns of the phosphor prepared in Example 5 and the calculated standard patterns. Figure 5 It can be seen that when the XRD spectrum of the phosphor prepared in Example 5 is compared with the standard spectrum of the standard SMAN, no impurity peak appears, that is, the phosphor synthesized in Example 5 is single-phase and has high purity.

[0078] Figure 6 (a) is the excitation spectrum and emission spectrum of the phosphor prepared in Example 5. Figure 6 The monitoring wavelength of the excitation spectrum in (a) is 676 nm. It can be seen that the phosphor prepared in Example 5 can be excited by wavelengths in the range of 250-380 nm and 400-500 nm. The excitation spectrum is a wide spectrum covering the ultraviolet and blue light regions. The excitation peak is located near 460 nm, and the spectrum peak is high, indicating that the phosphor prepared in Example 5 can be effectively excited by blue light. Figure 6 In the emission spectrum of (a), the excitation wavelength is 460nm and the emission peak is Eu 2+ The emission peak is located near 676 nm, the FWHM is 86 nm, and the color coordinates are (0.7065, 0.2934), which indicates that the phosphor prepared in Example 5 is suitable for making red phosphor for high color gamut laser display.

[0079] Example 6

[0080] According to the chemical formula SMAN-0.02LS:0.06Eu 2+The stoichiometric ratio of each raw material is as follows: Sr3N2, Mg3N2, Li3N, Si3N4, AlN and EuF3 (the purity of all raw materials is more than 99.5%) are weighed respectively, the raw materials are mixed to form a mixture, and after grinding and mixing evenly, the mixture is placed in a tungsten crucible, and then placed in a high-temperature and high-pressure furnace under a nitrogen atmosphere, the sintering pressure is 0.5MPa, and it is fired at 1300℃ for 6h, then cooled to room temperature, ground, and sieved to obtain a red nitride phosphor SMAN-0.02LS:0.06Eu 2+ (i.e. Sr2[Mg 1-x Li x Al 5-x Si x N7]:yEu 2+ , x=0.02, y=0.06).

[0081] Figure 5 (b, s) are the XRD patterns of the phosphor prepared in Example 6 and the calculated standard patterns. Figure 5 It can be seen that when the XRD spectrum of the phosphor prepared in Example 6 is compared with the standard spectrum of the standard SMAN, no impurity peak appears, that is, the phosphor synthesized in Example 6 is single-phase and has high purity.

[0082] Figure 6 (b) is the excitation spectrum and emission spectrum of the phosphor prepared in Example 6. Figure 6 The monitoring wavelength of the excitation spectrum in (b) is 680 nm. It can be seen that the phosphor prepared in Example 6 can be excited by wavelengths in the range of 250-380 nm and 400-500 nm. The excitation spectrum is a wide spectrum covering the ultraviolet and blue light regions. The excitation peak is located near 460 nm, and the spectrum peak is high, indicating that the phosphor prepared in Example 6 can be effectively excited by blue light. Figure 6 In the emission spectrum of (b), the excitation wavelength is 460nm and the emission peak is Eu 2+ The emission peak is located near 680nm, the FWHM is 87nm, and the color coordinates are (0.7075, 0.2924), which shows that the phosphor prepared in Example 6 is suitable for red phosphor for laser display.

[0083] Comparative Example 1

[0084] According to the chemical formula SMAN (Sr2[Mg1Al5N7]:yEu 2+ ):0.01Eu 2+The stoichiometric ratio of each raw material in the raw material is respectively weighed Sr3N2, Mg3N2, AlN and EuF3 (the purity of all raw materials is more than 99.5%), the raw materials are mixed to form a mixture, and after grinding and mixing evenly, they are placed in a tungsten crucible, put into a high-temperature and high-pressure furnace under a nitrogen atmosphere, the sintering pressure is 0.5MPa, and it is fired at 1300℃ for 6h, then cooled to room temperature, ground, and sieved to obtain a red nitride phosphor SMAN:0.01Eu 2+ .

[0085] Figure 7 The XRD spectrum of the phosphor prepared in Comparative Example 1 and the calculated standard spectrum are as follows: Figure 7 It can be seen that when the XRD spectrum of the phosphor prepared in Comparative Example 1 is compared with the standard spectrum of the standard SMAN, no impurity peak appears, indicating that the phosphor synthesized in Comparative Example 1 is single-phase and has high purity.

[0086] Figure 8 The excitation spectrum and emission spectrum of the phosphor prepared in Comparative Example 1 are shown. Figure 8 The monitoring wavelength of the excitation spectrum in is 657nm. It can be seen that the phosphor prepared in Example 1 can be excited by wavelengths in the range of 250-380nm and 400-500nm, and the excitation peak is located near 460nm; Figure 8 In the emission spectrum, the excitation wavelength is 460nm and the emission peak is Eu 2+ The emission peak is located near 657nm and the FWHM is 80nm. In addition, it is calculated that the external quantum efficiency of the phosphor sample prepared in Comparative Example 1 is only 28.1%, which is significantly lower than the sample prepared in Example 1 (42.0%).

[0087] Fig. 9 The thermal stability of luminescence of the phosphors prepared in Example 1 is compared with that of the phosphors prepared in Comparative Example 1. It can be seen that at 100-225°C, the thermal stability of luminescence of the phosphor prepared in Comparative Example 1 is significantly worse than that of the phosphor prepared in Example 1. The intensity of the phosphor prepared in Example 1 at 150°C is increased from 58.9% of that in Comparative Example 1 to 67.0%.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A red nitride phosphor, characterized in that: The chemical composition is Sr2[Mg 1-x Li x Al 5-x Si x N7]:yEu 2+ , where 0.001≤x≤0.50, 0.0005≤y≤0.

20.

2. The red nitride phosphor according to claim 1, characterized in that: x=0.02~0.4, y=0.01~0.

06.

3. The method for preparing the red nitride phosphor according to claim 1 or 2, characterized in that: The following steps are involved: According to the required stoichiometric ratio, a nitrogen-containing Sr source, a nitrogen-containing Mg source, a nitrogen-containing Al source, a nitrogen-containing Si source, a Li source and a Eu source are mixed and ground to obtain a mixed material; After sintering, the mixed material is ground and sieved in sequence to obtain red nitride phosphor.

4. The preparation method according to claim 3, characterized in that: The Li source is lithium nitride or lithium aluminum hydride; the Eu source is europium fluoride or europium nitride or europium oxide.

5. The preparation method according to claim 3 or 4, characterized in that: The sintering pressure is 0-1.0 MPa, and the sintering atmosphere is nitrogen or a nitrogen-hydrogen mixed gas.

6. The preparation method according to claim 5, characterized in that: In terms of volume percentage, the nitrogen-hydrogen mixed gas is a mixture of 90% nitrogen and 10% hydrogen.

7. The preparation method according to claim 6, characterized in that: The sintering temperature is 1100-1600° C., and the heat preservation time is 2-20 hours.

8. Use of the red nitride phosphor according to claim 1 or 2 or the red nitride phosphor prepared by the preparation method according to any one of claims 3 to 7 in a blue light excited laser display device.

9. Use of the red nitride phosphor according to claim 1 or 2 or the red nitride phosphor prepared by the preparation method according to any one of claims 3 to 7 in a blue light excited liquid crystal display.

Citation Information

Patent Citations

  • Nitrogen oxides luminescent material and preparation method thereof and lighting source made of same

    CN102559177A

  • Green fluorescent ceramic, and preparation method and application thereof

    CN113045205A

Cited By

  • Red nitride phosphor, and preparation method therefor and use thereof

    WO2026086758A1